PLN MOBILE APPLICATION PROMOTION STRATEGY IN FINANCIAL TRANSACTIONS AT PT. PLN (PERSERO) CUSTOMER SERVICE UNIT OF MEMPAWAH CITY - Marwaji; R. Luki Karunia; Rahayu (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Digital transformation in the electricity sector has encouraged PT. PLN (Persero) to launch the PLN Mobile application as a digital-based customer service platform. However, the implementation at the Customer Service Unit (ULP) in Mempawah City shows low adoption levels and financial transactions through the application. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) of the promotional strategies used and to formulate appropriate strategies to increase adoption and financial transactions. This research employed a descriptive qualitative approach with in-depth interview techniques involving PLN internal informants and customers. The findings reveal that the main strengths lie in the diversity of promotional media and the completeness of the application’s features, while weaknesses include low digital literacy, limited outreach, and reliance on conventional promotion. Opportunities exist through social media integration, community events, and loyalty programs, while threats come from limited digital infrastructure and customer resistance to behavioral change. Therefore, the formulation of promotional strategies is directed toward an integrated marketing communication (IMC) approach, combining digital marketing, face-to-face education, and community collaboration to enhance sustainable promotional effectiveness.